Implementation of Smart City in Palembang City - Mochammad Aidil Fikri; Isabella Isabella (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This study aims to examine the role of the Department of Communication and Informatics of Palembang City in developing a Smart City. According to a 2022 report from the Central Bureau of Statistics (BPS), approximately 50% of Palembang City residents have access to information regarding public services. This research uses a qualitative method with a descriptive approach. The author chose this approach to gain a deeper understanding of Smart City development in Palembang. The findings indicate that the roles of regulator, dynamizer, facilitator, innovator, and catalyst as outlined in the theory have been partially fulfilled. In addition, the Smart City indicators proposed by Mircea and Lucian namely technology, human resources, and institutional factors have started to be implemented. However, the development of a Smart City in Palembang still faces several challenges, such as limited infrastructure, low digital literacy, and a lack of synergy between government agencies and the community. With thorough planning, continuous innovation, and active participation from all stakeholders, Palembang has great potential to become one of the leading smart cities in Indonesia.In conclusion, the Palembang City Government, especially the Department of Communication and Informatics, needs to enhance its performance in the Smart City development effort by advancing technology and providing digital training to improve human resources. Furthermore, collaboration among local government agencies (OPD) is crucial to accelerating Smart City development in Palembang.